27=66x+6x+1+2

Simple and best practice solution for 27=66x+6x+1+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=66x+6x+1+2 equation:



27=66x+6x+1+2
We move all terms to the left:
27-(66x+6x+1+2)=0
We add all the numbers together, and all the variables
-(72x+3)+27=0
We get rid of parentheses
-72x-3+27=0
We add all the numbers together, and all the variables
-72x+24=0
We move all terms containing x to the left, all other terms to the right
-72x=-24
x=-24/-72
x=1/3

See similar equations:

| 5-(2x+3)=4x-10 | | 12.50+3/9=x | | 2x+(6x-7)=(103-x) | | 33=99-x | | 2(1/2x-6)=11 | | (x)=3x^2+1 | | 100=12x+13Y | | F(-5)=x^2-2x+7 | | (9x+16)(19x+3)(6x+15)=180 | | 3r=-42 | | 12.50+5/9=x | | 12=15n=33 | | 1x+1.2x-5.4=−10 | | 2({1}{2}x-6)=11 | | -28=x+4 | | 3(x-5)^2=363 | | 2/3x-8=x-17 | | 27=12x+6x+1+2 | | (2x+3)=(9x-25) | | 12(f+5)=138 | | 3(x–5)=2x–3 | | 4g-36=-12 | | 27=12x+1+2 | | -18=-9c | | 3+5x=(4x+7)=4(7x+3)-3 | | 9x44+6x+3=77 | | 1.2*8.5=1.7x | | -3x+4=5x+7 | | 2*x1x=49 | | -4.5+4.5=+y3 | | n=17.53-n | | 11+1x+22=67x+33 |

Equations solver categories